Metabolic control during the SARS‐CoV‐2 lockdown in a large German cohort of pediatric patients with type 1 diabetes: Results from the DPV initiative. Issue 3 (14th February 2022) - Hammersen, Johanna; Reschke, Felix; Tittel, Sascha R.; Pappa, Angeliki; Dost, Axel; Köstner, Katharina; Rosenbauer, Joachim; Kapellen, Thomas M.; Rohrer, Tilman R.; Holl, Reinhard W.
Abstract: Objective: To assess if metabolic control worsened during the SARS‐CoV2 lockdown in spring 2020 in youth with type 1 diabetes (T1D) in Germany. Methods: Data from 19, 729 pediatric T1D patients from the diabetes prospective follow‐up (DPV) registry were available. Data sets from four time‐periods between January 1 and June 30, 2020, were compared with data from the whole year 2019 in the same patient; differences were adjusted for seasonality, increasing age, and longer diabetes duration. HbA1c values from laboratory measurements and estimates derived from continuous glucose monitoring (CGM) were aggregated into a combined glucose indicator (CGI), expressed in analogy to HbA1c. Results: Based on regression models adjusted for differences of sex, age, diabetes duration, and migratory background between the four time‐periods, CGI values in 2020 were slightly higher than in 2019, for example, by 0.044% (0.042–0.046) (median [95% CI]) in the second lockdown month, time‐period 3. Insulin dose and BMI‐SDS were also marginally higher. In 2020, there were fewer hospitalizations (e.g., incidence risk ratio in time‐period 3 compared with 2019: 0.52 [95% CI: 0.46–0.58]). In a subgroup of patients reporting CGM data in both years, metrics in 2020 improved: time in target increased, and mean sensor glucose fell, for example, by 2.8% (2.7–2.9), and by 4.4 mg/dl (4.3–4.6) in time‐period 3. Conclusion: Before, during, and after the lockdown in spring 2020, metabolic control in youth with T1D in Germany did not differ significantly from the preceding year. Further effects of the ongoing pandemic on pediatric T1D patients need to be evaluated.